Addressing Gender Issues in Education, Training for Vietnam’s Ethnic Minorities - Minh Đức Trần (CV. Era Digital Nusantara, 2025)
Abstract: Gender equality in education is a crucial factor in achieving sustainable development. Although Vietnam has actively participated in international agreements on gender equality and education, disparities persist, particularly among ethnic minority communities. Ethnic minority women face greater obstacles than men due to cultural norms, economic constraints, and policy limitations. These barriers result in lower participation rates and higher dropout rates among female students, especially at the secondary and higher education levels. Addressing these challenges requires comprehensive policies that are both gender-sensitive and culturally inclusive. Purpose: This study aims to examine the factors contributing to gender inequality in education among ethnic minority communities in Vietnam. It identifies cultural, economic, and policy-related barriers that hinder female students' educational opportunities and explores potential solutions to enhance gender equality in education. Design/Methodology/Approach: A mixed-methods approach was employed, combining qualitative and quantitative data collection. Primary data were gathered through interviews and surveys with students, educators, and policymakers in ethnic minority regions. Secondary data from government reports and international organizations provided additional insights into the systemic challenges affecting gender equality in education. Findings: The study reveals that approximately 45% of ethnic minority female students drop out before completing lower secondary education, primarily due to early marriage customs, household responsibilities, and traditional gender roles. Economic hardships, geographical distance, and inadequate educational infrastructure further exacerbate the issue. Although government policies provide financial aid and scholarships, they lack gender-sensitive provisions addressing the specific needs of ethnic minority women. Initiatives by organizations such as Irish Aid, UNDP, and UNICEF have contributed to improving educational access, but their effectiveness depends on stronger coordination with local authorities. Originality/value: This study contributes to the discourse on gender equality in education by highlighting the unique challenges faced by ethnic minority women in Vietnam. It emphasizes the need for gender-responsive education policies, community awareness programs, and flexible vocational training initiatives to promote inclusive and sustainable educational opportunities. The findings offer valuable insights for policymakers, educators, and international organizations working toward gender equality in education.